Analisis Semantik Pada Puisi “Aku Ingin” Karya Sapardi Djoko Darmono: The Analysis of Semantics on The Poetry “Aku Ingin” From Sapardi Djoko Darmono - Kristianti, Ola; Sulastri, Saptiana (Balai Bahasa Provinsi Papua, 2024)
This study aims to describe and find out about semantic studies that focus on grammatical meaning, lexical meaning, referential meaning and figurative meaning in the poem